High-rise [videorecording (DVD)] - Irons, Jeremy, 1948-; Hiddleston, Tom; Miller, Sienna, 1981-; Moss, Elisabeth, 1982-; Ballard, J. G., 1930-2009 (2016)
Dr. Robert Laing is the newest resident of a luxurious apartment in a high-tech concrete skyscraper whose lofty location places him amongst the upper class. But as power outages become more frequent and building flaws emerge, particularly on the lower floors, the regimented social strata begins to crumble and the building becomes a battlefield in a literal class war.